2017
DOI: 10.1177/2050640617707864
|View full text |Cite
|
Sign up to set email alerts
|

Fluid resuscitation with lactated Ringer’s solution vs normal saline in acute pancreatitis: A triple-blind, randomized, controlled trial

Abstract: Lactated Ringer's is associated with an anti-inflammatory effect in patients with acute pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
102
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(117 citation statements)
references
References 39 publications
9
102
0
6
Order By: Relevance
“…revealed that Ringer's lactate was associated with the decreased persistence of SIRS, and similar results were shown in a study by Wu et al . which supports the anti‐inflammatory effects of Ringer's lactate . C‐reactive protein is a cost‐effective, widely used non‐specific inflammatory marker and various studies have shown it as a useful predictor of the severity of AP .…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…revealed that Ringer's lactate was associated with the decreased persistence of SIRS, and similar results were shown in a study by Wu et al . which supports the anti‐inflammatory effects of Ringer's lactate . C‐reactive protein is a cost‐effective, widely used non‐specific inflammatory marker and various studies have shown it as a useful predictor of the severity of AP .…”
Section: Discussionmentioning
confidence: 65%
“…Most of these 19 studies were reports of a comparison between Ringer's lactate with normal saline in post‐ERCP pancreatitis. Finally, five studies including 428 participants met the eligibility criteria. Two of the included studies were retrospective observational cohort studies and three were RCTs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Goal-directed rehydration with Ringer’s lactate solution (or Hartmann’s) is recommended31 at a rate of 5–10 mL/kg/hour until resuscitation goals are reached 26. A recent triple-blind RCT compared Ringer’s lactate to normal saline in AP and found that Ringer’s lactate was associated with an anti-inflammatory effect which was attributed to the properties of lactate 32. A urinary catheter should be inserted in severe AP in order to record accurate fluid balance.…”
Section: Initial Resuscitationmentioning
confidence: 99%